Akulturasi Budaya Dalam Tradisi Pattutoang Di Desa Bontomate’ne Kecamatan Turatea Kabupaten Jeneponto - Anisa, Putri; Junaeda, St. (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2024)
This study aims to determine: the process of implementing the Pattutoang tradition, the community's view of the pattutoang tradition, and the existence of the pattutoang tradition in Bontomate “ne Village. In this study, descriptive qualitative research was used. The data collection techniques were carried out using observation, interview, and documentation methods. Based on the results of the study showed that: (1) the process of implementing the pattutoang tradition has 3 stages, namely the determination of the place, the preparation stage and the implementation stage, and provides various types of food in one assembly to be washed away. (2) the community's view of the pattutoang tradition is very important in order to avoid bala (calamity) or bad luck and as a form of respect and respect for the traditions of their ancestors. (3) the existence of the pattutoang tradition until now continues to be carried out among the community because it remembers and appreciates existing traditions as a legacy from ancestors and has become a habit of the people in Bontomate “ne Village even though the way of implementation has changed.